TEACHER’S LEARNING STRATEGY FOR RECOGNIZING THE CHILDREN’S CONCEPT OF NUMBERS - Aisyah, Siti; Agusta, Akhmad Riandy; Santika, Viona; Patriamurti, Yudhita Dwi; Putri, Salta Virgaria (E-CHIEF Journal, 2024)
The problem in this study is the low cognitive development of number concept children. The solution to this problem is to use the Project visualization model. The purpose of this study is to describe the activity of teachers, analyze children's activities and cognitive development. This research uses a qualitative approach with the type of Classroom Action Research (CAR), which is carried out with four meetings. The subjects of the study were group A children of Tunas Muda Kindergarten, the number of children was 13 people. The type of data in this study is qualitative data. The results of this study showed that teacher activities at meeting I got a score of 32, meeting II got a score of 42, meeting III got a score of 48, and meeting IV got a score of 52. Children's activities at meeting I obtained a percentage of 53.84%, meeting II obtained a percentage of 68.50%, meeting III obtained a percentage of 83.17%, and meeting IV obtained a percentage of 94.95%. Cognitive Development of children meeting I obtained a percentage of 75.96%, meeting II obtained a percentage of 82.05%, meeting III obtained a percentage of 89.10%, and meeting IV obtained 96.15%. Based on the results of the study, it can be concluded that teacher activity, child activity, and child development results have successfully increased and developed.